Pengembangan Kecerdasan Spiritual Anak Melalui Amalan Ibadah Puasa Ramadhan Sejak Masa Dini - Carina Septiani; Fathimah Az-Zahra Binti Idratul Amri; Saidah Syakira; Zahra Dalvinova; Wismanto Wismanto (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
It cultivates values, meaning, purpose, and a sense of connectedness in their lives. 'We must prioritize the cultivation of children's spiritual intelligence as it plays a vital role in fostering their values, purpose, meaningfulness, and a feeling of interconnectedness in their existence. 'Kids represent the future. One's commitment to self-reflection, meditation, and exploring one's inner self.' Various factors contribute to this, including the practice of fasting during Ramadan. Children are taught how to observe Ramadan. Adhering to the child's level of development and capability when it comes to fasting. achievements in children's development spiritual intelligence can be assessed through indicators of spiritual intelligence as well as the values that it impacts. Nurturing children's spiritual intelligence at a young age by encouraging them to practice fasting during the holy month of Ramadan. The research methodology employs a qualitative method. The methods employed to gather data through observing, interviews & documentation.